Preparation of novel Au-Nb3O7F nanosheets for the photodegradation of tetracycline hydrochloride - Wang, Zhiyuan; Ren, Li; Chen, Zhi; Chen, Yao; Tian, Xin; Wei, Guoying (Frontiers in Chemistry, 2024)
Water pollution caused by antibiotics is a growing problem and photodegradation by efficient catalysts is an environmentally friendly technology that can effectively degrade organic pollutants in water. Here, a novel method was innovatively used to synthesize niobium oxyfluoride (Nb3O7F) nanosheets decorated with Au nanoparticles, which is the first report for the composites of Au and Nb3O7F. We prepared the Nb3O7F nanosheets via hydrothermal synthesis followed by deposition of Au nanoparticles on their surface using HAuCl4. The prepared samples were characterized by XRD, HRTEM, XPS, and UV–Vis. The diameters of most Au NPs are ranging from 5 to 25 nm with an average size of about 16.9 nm, as well as the Nb3O7F nanosheets in size ranging from 200 nm to 700 nm. The chemical composition of the Au-Nb3O7F showed a Au/Nb atomic ratio of 1/10, as well as a Nb/O/F ratio of 3/7/1. UV–Vis spectrum reveals a largest absorption peak at 520 nm for the Au-Nb3O7F nanosheets. The prepared Au-Nb3O7F nanomaterials were applied to the visible-light photodegradation of tetracycline hydrochloride, with the photocatalytic degradation rate reached more than 50% under the optimal conditions within 1 h. Capture experiments indicated that h+ and •O2- are the main active substances involved during the course of the photodegradation. Furthermore, the proposed mechanism for the photodegradation of the novel Au-Nb3O7F nanosheets was given.